2013
DOI: 10.1111/ppa.12066
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae pv. actinidiae: chemical control, resistance mechanisms and possible alternatives

Abstract: Pseudomonas syringae pv. actinidiae (Psa) is a Gram-negative bacterium that causes the bacterial canker of both green (Actinidia deliciosa) and yellow (Actinidia chinensis) fleshed kiwifruit. Since the emergence of an economically devastating Psa outbreak in Japan in the 1980s, the disease took a contagious turn causing severe economic loss to kiwifruit industries in Italy, South Korea, Spain, New Zealand and other countries. Research shows that the pathogenic strains isolated from different infected orchards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
90
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 77 publications
(166 reference statements)
0
90
2
Order By: Relevance
“…Hayward, by using chemical and biological products. Chemical control of bacterial diseases, and particularly of Psa, is highly dependent on spraying antibiotics, such as streptomycin, or copper formulations (Cameron and Sarojini 2014). In Europe the use of streptomycin for control of plant pathogens is not legal, so copper formulations remain the main management strategy for crop protection against bacterial diseases (Gullino and Brunelli 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Hayward, by using chemical and biological products. Chemical control of bacterial diseases, and particularly of Psa, is highly dependent on spraying antibiotics, such as streptomycin, or copper formulations (Cameron and Sarojini 2014). In Europe the use of streptomycin for control of plant pathogens is not legal, so copper formulations remain the main management strategy for crop protection against bacterial diseases (Gullino and Brunelli 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, copper spraying has become a significant component of the kiwifruit industry’s spray program for providing protection against infection by Pseudomonas syringae pv. actinidiae (Cameron and Sarojini, 2014; Gould et al, 2015). Similarly, copper fungicides are widely used by the New Zealand forestry industry for control of dothistroma needle blight (Bulman et al, 2013) and they have recently been shown to be effective against Phytophthora pluvialis (Rolando et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Products such as harpins that activate plant defence and induce resistance, and polysaccharides such as chitosan (Dong et al, 1999;Reglinski et al, 2011) have been used to control different bacterial pathogens. In addition, terpenes (Ferrante & Scortichini, 2010) and antimicrobial peptides (Cameron & Sarojini, 2014) are reported to control phytopathogenic Pseudomonas syringae to some extent. Several other chemicals have been proposed and used for the control of bacterial diseases.…”
Section: Disease Managementmentioning
confidence: 99%